Final infiltration rate as an indicator for soil erodibility prediction - Aburas, Murad M. (Al-Mukhtar Journal of Sciences, 2012)
Erodibility-related soil properties such as silt, sand and clay contents, organic matter content and final infiltration rate were statistically tested. Silt + very fine sand and clay percentage were the most correlated to the predicted values of soil erodibility. Final infiltration rate was relatively less correlated, while organic matter percentage was the least correlated property to the predicted erodibility. According to the regression analysis, soil fractions especially silt + very fine sand were the most significant factor that determines predicted soil erodibility. However, actual field measurements showed that measured soil erodibility was more influenced by infiltration rate compared to soil fractions. Supported by similar results from the Mediterranean region, this paper concluded that the application of infiltration rate as an indicator of erodibility for shallow Red Mediterranean soils can be more reliable than other common indicators.